Propriety of judiciary staff union of Nigeria strike towards securing the financial autonomy of the judiciary in Nigeria (2021)
This paper adopts the doctrinal methodology in appraising the propriety of the JUSUN strike embarked upon to compel State Governments to' recognise the financial autonomy of the judiciary. Thus, strike action is a last deployed by employees to compel their employer to grant their demands; it is a corollary of the right to freedom of association guaranteed by the 1999 Constitution of the Federal Republic of Nigeria (1999 CFRN). The paper examines the provision of the Trade Disputes Act (TDA) as to the prerequisite and grounds upon which employees can embark on strike action, the meaning of trade dispute to ascertain whether the dispute that led to JUSUN strike is a trade dispute. The paper found that, while employees are legally permitted, upon fulfilment of certain conditions, to embark on strike, the strike embarked upon by JUSUN, does not come within the ambit of sections 18, 43 and 48 of the TDA and the dispute pursuant to which the strike is anchored, is not a trade dispute hence, same is therefore illegal It argues that; while judicial officers are unable to "unionise" and embark on strike, the category of judicial staff who are directly affected by the lack of financial autonomy of the judiciary, are regarded as projection of management and therefore ineligible to join or form trade union (JUSUN). Also, despite embarking on an illegal strike, members of JUSUN are paid salaries notwithstanding the provision of the TDA. Giving the commitment shown by the Nigeria Governors Forum (NGF), the Nigerian Bar Association (NBA) and other sympathising stakeholders should implore JUSUN to call of the strike or governors should invoke no work, no pay rule.